If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 26y = 14 Solving 2x + 26y = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26y' to each side of the equation. 2x + 26y + -26y = 14 + -26y Combine like terms: 26y + -26y = 0 2x + 0 = 14 + -26y 2x = 14 + -26y Divide each side by '2'. x = 7 + -13y Simplifying x = 7 + -13y
| -1=x/-6 | | 16-x=x+6 | | 3(4u-4)=5[-2u+2(-u-3)] | | 4yx+3yx= | | -6*(1-4*x)^1/2=-30 | | -2(7x+4)=-120 | | y=5/2(4)-2 | | 4+5(4k-4)=104 | | -3b-3b=12 | | 4y+3x=11 | | -13y-26=7y+22 | | 8x+20=5x+35 | | 3x-7y+6z=5 | | X^8=1/12 | | 16/5x=1/10 | | x-5y=-2 | | 9=2w+5 | | -8n-3=-27 | | 3(3x-3)-28=4x-2 | | 3/2*(1-4x)^1/2=-30 | | (((3x-1/4)^2))^4 | | 5x-12=10-6x | | FxD=F | | 11/2*31/2*23/4 | | 4=-6+x | | A+C=A | | 6+9=3x | | -30=3r | | 38=7b+10 | | 2(x-1)=10(1-x)+6 | | 3xy+4xy-xy= | | 4x+29=5-8(x+6) |